How do people experience the temporality of everyday life changes? Towards the exploration of existential time in HCI. Issue 167 (November 2022) - Rapp, Amon
Highlights: I explore how people account for and experience the temporalities of their daily life changes through 16 semi-structured interviews. I highlight that the velocity, direction, and synchronization of time impact on how individuals perceive and manage their own changes, while technology plays a minor role. I emphasize that "existential time" of change can be shaped by the individuals themselves and is often open to others despite its fundamental subjectivity. I move the HCI debate on time beyond the dichotomies between slowness and speediness, as well as between objective and social times. I propose suggestions for designing temporal technologies that make the velocity of change malleable, support the ascription of meaning to the direction of time, and encourage people to share their temporal experiences with others. Abstract: The idea of time as an existential concern has found scarce attention in the Human-Computer Interaction (HCI) community. Still, time in our life is mostly experienced in connection with important existential matters. Life changes are emblematic examples of aspects of our existence that are fundamentally temporal. In this article, I explore how people experience the temporalities of "change", by asking 16 participants to report on life changes they consider relevant and their temporal aspects. I found that temporal features like velocity, direction, and synchronization deeply impact the process of change, by affecting the participants' opportunities to make sense of and act upon their own transformations. The study findings point to a conception of existential time that contributes to both HCI research on time and life changing events, by highlighting the relativity of temporal slowness and speediness, the malleability of time, and the fundamental openness of our time experiences.